1992
DOI: 10.1111/j.1365-2249.1992.tb06871.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of the long (S) allotype of CR1 (the C3b/C4b receptor, CD35) in patients with systemic lupus erythematosus

Abstract: SUMMARYTbe allotypic forms ofthe C3b/C4b receptor (CRl, CD35) differ in length, in the number of expressed C3b binding sites and thus in their ability to mediate the processing of circulating C3-and C4-bearing immune complexes. We have used a combination of three informative restriction fragment length polymorphisms (RFLPs) to assess the frequencies of the F (most frequent allele comprised of four long homologous repeats (LHR)), S (five LHR) and F' (three LHR) alleles ofthe C3b/C4b receptor (CRl, CD35) in a Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 21 publications
(41 reference statements)
0
1
0
2
Order By: Relevance
“…The fundamental role of CS in autoimmunity is clearly reflected in the fact that genetic deficiency of C1q or C4 – and other complement components – is a major predisposing factor for severe SLE [ 23 ], while S allele of CR1 has been genetically linked with this disease [ 69 ]. The main potential mechanism includes the release of self-antigens due to failure in the regulation of complement response to apoptosis [ 70 , 71 ], as well as the formation of IC between AAb and self-antigens against tissues, leading to activation primarily of the classic pathway [ 27 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental role of CS in autoimmunity is clearly reflected in the fact that genetic deficiency of C1q or C4 – and other complement components – is a major predisposing factor for severe SLE [ 23 ], while S allele of CR1 has been genetically linked with this disease [ 69 ]. The main potential mechanism includes the release of self-antigens due to failure in the regulation of complement response to apoptosis [ 70 , 71 ], as well as the formation of IC between AAb and self-antigens against tissues, leading to activation primarily of the classic pathway [ 27 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Τα ερυθρά του αρρώστου και μια μικρή ποσότητα ορού επωάζονται σε διάλυμα σουκρόζης χαμηλής ιοντικής ισχύος η οποία ευοδώνει τη καθήλωση του συμπληρώματος στην μεμβράνη των ερυθρών [Hartmann et al 1970]. H ευόδωση της ενεργοποίησης του καταρράκτη του συμπληρώματος οφείλεται είτε σε αντίδραση αντιγόνου-αντισώματος ή σε ενεργοποίηση της εναλλακτικής οδού του συμπληρώματος [Jenkins 1972, Götze & Müller-Eberhard 1972 [Cornillet et al 1992]. Ο κύριος υποκείμενος μηχανισμός περιλαμβάνει δυνητικά την ανεξέλεγκτη απελευθέρωση αυτοαντιγόνων στην κυκλοφορία, λόγω της ανεπαρκούς ρύθμισης του ενεργοποιημένου συμπληρώματος κατά την απόπτωση [Nauta et al 2003, Munoz et al 2010, όπως επίσης και τον σχηματισμό ανοσοσυμπλεγμάτων μεταξύ αυτοαντισωμάτων και αυτοαντιγόνων, τα οποία εναποτίθενται στους αυτόλογους ιστούς και τα όργανα (όπως το νεφρικό σπείραμα), προκαλώντας την ενεργοποίηση της κλασσικής οδού του συμπληρώματος [Walport 2001(b), Ferreira et al 2010.…”
Section: 2 β β δ δο οκ κι ιμ μα ασ σί ία α τ το ου υ ο οξ ξυ υν νι ισ σθ θέ έν ντ το ος ς ο ορ ρο ού ύ ( (H Ha Am M T Te Es St T) )unclassified
“…Σύμφωνα με τη μοντέλο της «διπλής θεωρίας» [Rotoli & Luzzato 1989, τα ευρήματα σε οστεομυελικές βιοψίες ασθενών με SLE και κυτταροπενίες, χωρίς να λαμβάνουν ανοσοκατασταλτική θεραπεία [Feng et al 1991, Pereira et al 1998, καθώς και η παρουσία αυτοαντισωμάτων έναντι μυελικών προγονικών αιμοποιητικών κυττάρων σε σπάνιες περιπτώσεις ασθενών με SLE και ΑΑ [Brooks et al 1984, Baily et al 1989, ενισχύουν την θεωρία ενός πρωτοπαθούς συνδρόμου αιμοποιητικής ανεπάρκειας ανοσολογικής αρχής, υποδηλώνοντας πως υπάρχει μια ανοσορυθμιζόμενη θετική επιλογή επιβίωσης του GPI(-) ερυθροκυτταρικού κλώνου, ο οποίος πολλαπλασιάζεται επιλεκτικά, σε σύγκριση με τη φυσιολογική αιμοποίηση, μέσα σε ένα μικροπεριβάλλον ανοσολογικής επίθεσης στο μυελό των οστών, ως ότου γίνει ανιχνεύσιμος με την μεθοδολογία του SGT [Nathalang et al 2003, Gupta et al 2007. [Lach-Trifilieff et al 1999] θεωρείται από πολλούς ερευνητές ότι συμβάλλει σημαντικά στην παθοφυσιολογία πολλών αυτοάνοσων διαταραχών, όπως ο SLE και η RA [Ross et al 1985, Cohen et al 1992, καθώς επίσης και πως αντανακλά την ενεργότητα της νόσου και την κατάσταση της φλεγμονής, κατέχοντας σημαντικό ρόλο στην μεσολαβούμενη από τα C3 και C4 κλάσματα του συμπληρώματος κάθαρση των ανοσοσυμπλεγμάτων από την κυκλοφορία [Holme et al 1986, Arora et al 2000, Birmingham et al 2005, Arora et al 2007 CONCLUSION This study provides sufficient evidence supporting the presence of "PNHlike" erythrocytes in patients with rheumatic disorders. Moreover, it was demonstrated that CD55-deficiency on red cells influences the levels of Hb, but not the presence of anemia, in these patients.…”
Section: 2 β β δ δο οκ κι ιμ μα ασ σί ία α τ το ου υ ο οξ ξυ υν νι ισ σθ θέ έν ντ το ος ς ο ορ ρο ού ύ ( (H Ha Am M T Te Es St T) )unclassified